Small cell variant of renal oncocytoma--a rare and misleading type of benign renal tumor - Hes, O; Michal, M; Boudova, L; Mukensnabl, P; Kinkor, Z; Miculka, P (International journal of surgical pathology, 2001)
Here we report 3 cases of renal oncocytoma with a dominating small cell component arising in adult women. These 3 cases of small cell variant of renal oncocytoma were found among 134 cases of oncocytomas of the kidney in the routine and consultation files of the authors. Two of 3 cases were initially thought to be a malignant tumor by the referring pathologists. In all 3 cases minor areas of the tumors, which were identical to the classical renal oncocytomas were found. The small cell areas were arranged in a characteristic organoid pattern different from all the known types of the renal benign and malignant tumors. We summarize all morphologic, immunohistochemical, and ultrastructural features of this unusual oncocytoma variant with regard to its differential diagnosis. Int J Surg Pathol 9(3):215-222, 2001
Keywords: Adult; Female; Adenoma, Oxyphilic; Immunohistochemistry; Biomarkers; dospělí; biologické markery; oxyfilní adenom; nádory ledvin; ženské pohlaví; Humans; lidé; imunohistochemie; senioři; Aged; Kidney Neoplasms